2017
DOI: 10.1186/s13063-016-1774-6
|View full text |Cite
|
Sign up to set email alerts
|

Abelmoschus manihot – a traditional Chinese medicine versus losartan potassium for treating IgA nephropathy: study protocol for a randomized controlled trial

Abstract: BackgroundIgA nephropathy (IgAN) is one of the most common primary glomerular diseases worldwide, but effective therapy remains limited and many patients progress to end-stage renal disease (ESRD). Only angiotensin-converting enzyme inhibitors (ACE-I)/angiotensin-receptor blockers (ARB) show a high level of evidence (1B level) of being of value in the treatment for IgAN according to the 2012 Kidney Disease: Improving Global Outcomes (KDIGO) guidelines. However, traditional Chinese medicine has raised attention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 24 publications
(23 reference statements)
0
18
0
Order By: Relevance
“…HKC and its bioactive component hyperoside (HYP) can ameliorate proteinuria and renal dysfunction for patients and animal models with the early chronic kidney disease (CKD) (Chen et al, 2015 ; Ge et al, 2016 ). Recently, the increasing clinical evidences in China have been suggested that HKC at the safe and effective dose of 7.5 g/kg/day can reduce micro-urinary albumin (micro-UAlb) in the early DN patients and the IgA nephropathy patients (Liu et al, 2010 ; Li et al, 2017 ), and that its therapeutic action may be concerned with regulating transforming growth factor-β1 (TGF-β1) signaling in vivo (Tu et al, 2013 ), and inhibiting high-glucose (HG)-induced renal tubular epithelial-mesenchymal transition in vitro (Cai et al, 2017 ). In addition, our previous animal experiment as the first step revealed that, after the drug-intervention for 8 weeks, 2 g/kg/day dose of HKC can significantly attenuate the advanced renal fibrosis in the DN model rats induced by the unilateral nephrectomy combined with the intraperitoneal injection of streptozotocin (STZ) through regulating oxidative stress and p38 mitogen-activated protein kinase/Akt pathways (Mao et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…HKC and its bioactive component hyperoside (HYP) can ameliorate proteinuria and renal dysfunction for patients and animal models with the early chronic kidney disease (CKD) (Chen et al, 2015 ; Ge et al, 2016 ). Recently, the increasing clinical evidences in China have been suggested that HKC at the safe and effective dose of 7.5 g/kg/day can reduce micro-urinary albumin (micro-UAlb) in the early DN patients and the IgA nephropathy patients (Liu et al, 2010 ; Li et al, 2017 ), and that its therapeutic action may be concerned with regulating transforming growth factor-β1 (TGF-β1) signaling in vivo (Tu et al, 2013 ), and inhibiting high-glucose (HG)-induced renal tubular epithelial-mesenchymal transition in vitro (Cai et al, 2017 ). In addition, our previous animal experiment as the first step revealed that, after the drug-intervention for 8 weeks, 2 g/kg/day dose of HKC can significantly attenuate the advanced renal fibrosis in the DN model rats induced by the unilateral nephrectomy combined with the intraperitoneal injection of streptozotocin (STZ) through regulating oxidative stress and p38 mitogen-activated protein kinase/Akt pathways (Mao et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that HKC might be a promising agent for patients with primary kidney disease and moderate proteinuria, especially in CKD stages 1 and 2 ( Carney, 2014 ; Zhang et al., 2014 ). Li et al. (2017) assessed the efficacy and safety of HKC for treating immunoglobulin A (IgA) nephropathy in a multicenter, prospective, double-blind, and double-dummy randomized controlled clinical trial by enrolling approximately 1600 patients with biopsy-proven IgA nephropathy at 100 centers and following them for up to 48 weeks.…”
Section: Clinical Settingsmentioning
confidence: 99%
“…The results of this study indicated that HKC (at a dose of 2.5 g [i.g.] three times per day) markedly decreased 24 h urinary protein and the estimated glomerular filtration rate with respect to baseline after treatment for 48 weeks ( Li et al., 2017 ). In addition, two systematic reviews and a meta-analysis were conducted to determine the safety and efficacy of HKC for the treatment of DN and type 2 DN, respectively.…”
Section: Clinical Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…More and more traditional Chinese medicine (TCM) has been used for prevention and treatment of IgAN and gradually approved worldwide ( Li et al., 2017 ; Li and Li, 2020 ). Zhen-wu-tang (ZWT) is a classical prescription of Treatise on Febrile Diseases written by Zhongjing Zhang, composed of Aconiti Lateralis Radix Praeparata, Poria, Atractylodis Macrocephalae Rhizoma, Paeoniae Radix Alba and Zingiberis Rhizoma Recens .…”
Section: Introductionmentioning
confidence: 99%